Budgeting Costs and Returns for Indian River Citrus Production, 2004-05 - Ronald P. Muraro; John W. Hebb (EDIS, 2006)
FE630, a 37-page report by Ronald P. Muraro and John W. Hebb, is the 22nd year of the report. It is intended to be used for budgeting costs and returns by individual growers in citrus producing counties on Florida's east coast, including Brevard, Indian River, Martin, Palm Beach, and St. Lucie Counties. Published by the UF Department of Food and Resource Economics, September 2005.